The evolution of rule of law in Cambodia. Issue 1 (2nd January 2017) - McCarthy, Stephen; Un, Kheang
ABSTRACT: Cambodian leaders have confounded the efforts of the international community to promote rule of law. Over the past decade the Cambodian government has introduced a series of legal reforms and overseen an increase in the use of legal proceedings including defamation lawsuits against opposition politicians and members of civil society. These reforms and practices, as well as the role of the judiciary in relation to each, may be better understood through elite perceptions of the rule of law in Cambodia. Comprehending the rule of law as it is understood by the ruling elites offers better insight into the trajectory of legal development and the obstacles to Western ideals for legal reform. This article situates Cambodia within the context of illiberal democracy and examines how a thin rule of law has evolved, focusing on defamation law as a legal and political strategy of control. While the international community has pressed Cambodia to carry out liberal legal reforms for some time, the article will outline the obstacles facing reformers and the competing desires of Cambodian leaders embedded in the patronage based political order.